1999
DOI: 10.1142/s0217979299001132
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Biaxially Oriented NI-V Substrate

Abstract: The paper presents the structural and magnetic properties of a new non-magnetic biaxially textured substrate based on Ni 100-x V x solid-solution for YBa 2 Cu 3 O 7-y tape fabrication. The effective atomic magnetic moment monotonously decreases with the vanadium concentration, causing a corresponding decrease of Curie temperature. The Curie temperature reaches the zero value at about 11.5. % of vanadium. The texturing studies revealed that (100)[001] cube texture can be easily developed up to x=11 at. %, by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The (001)[100] cube texture was induced in Ni 89 V 11 alloy by rolling the Ni-V bar at room temperature followed by recrystallization annealing in vacuum under 10 −6 Torr at 900 • C for 4 h. Detailed information about the preparation and magnetic and mechanical properties of Ni-V substrates is published elsewhere [7,11,12]. Unlike pure Ni, which only under special conditions forms (00l)-oriented NiO [13], it has been observed that, within a large range of oxygen pressure and temperature, the NiO is epitaxially formed on the Ni-V substrates, for vanadium concentrations greater than 7 at%.…”
Section: Methodsmentioning
confidence: 99%
“…The (001)[100] cube texture was induced in Ni 89 V 11 alloy by rolling the Ni-V bar at room temperature followed by recrystallization annealing in vacuum under 10 −6 Torr at 900 • C for 4 h. Detailed information about the preparation and magnetic and mechanical properties of Ni-V substrates is published elsewhere [7,11,12]. Unlike pure Ni, which only under special conditions forms (00l)-oriented NiO [13], it has been observed that, within a large range of oxygen pressure and temperature, the NiO is epitaxially formed on the Ni-V substrates, for vanadium concentrations greater than 7 at%.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation and properties of Ni-V substrate are reported elsewhere [8,9]. Buffer layers were deposited by both pulsed laser deposition (PLD) and electron beam evaporation (e-beam) techniques starting from stoichiometric targets.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, Ni is one of the few elemental ferromagnets (FM) with a high critical temperature T c = 630 K 6 while on the other hand the magnetism of Ni is very sensitive to changes in the local environment caused by other elements that weaken the magnetic moment and the magnetic order. It is known that T c is easily tuned 7 in Ni 1−x X x by partial chemical substitution of Ni with another d-element X down to very low values. Ni-alloys seem to provide a good opportunity for observing magnetic quantum phase transitions (QPT) by reducing the FM ordering temperature T c down to zero and leaving a paramagnetic phase (PM) without magnetic order.…”
Section: Introductionmentioning
confidence: 99%